Sonodynamic and magnetic targeting platelet-membrane biomimetic platform for glioblastoma therapy - Zou, Shibin; Zhang, Yueyang; Mao, Shanyong; Yuan, Mengxia; Yang, Jie (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundDue to the presence of the blood-brain barrier, the efficacy of chemotherapy for glioblastoma has remained suboptimal. Even drugs capable of crossing the BBB, such as temozolomide, exhibit limited therapeutic outcomes owing to insufficient targeting.MethodsHere, we developed a platelet membrane-hybridized biomimetic microbubble by loading superparamagnetic iron oxide and temozolomide-embedded polymers, constructing an ultrasound-controlled platelet membrane-inspired magnetic targeting drug delivery platform (ST-PM). Extensive in vitro and in vivo experimental results demonstrate that ST-PM exhibits inhibitory effects on glioblastoma under the combined action of a magnetic field and focused ultrasound.ResultsThe results demonstrated that ST-PM significantly enhanced microbubble stability in vivo while preserving both the magnetic targeting capability of magnetic drugs and the ultrasound-sensitizing properties of microbubbles. In orthotopic tumor mouse models, ST-PM exhibited superior tumor-targeting efficiency and markedly inhibited tumor growth. Furthermore, H&E staining of major organs confirmed the biosafety of ST-PM.ConclusionThe platelet membrane enhances the stability of drug-loaded microbubbles, facilitating targeted drug accumulation at the lesion site. These findings propose a novel treatment strategy with clinical translation potential for glioblastoma management.